The impact of gender on individual decisions: Evidence from the "Millionaire Show" - Erik E. Lehmann; Susanne Warning (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2003)
In order to analyse whether women and men differ in their decision making under risk and uncertainty, we use data from the game show 'Who Wants to be a Millionaire?'. It turns out that i) there are gender differences in choosing a lottery or a certain value only for 'largestakes' lotteries, ii) the decision making process differs significantly between 'small' and 'large' stake lotteries for both women and men, and iii) people with lower income tend to react more reluctant to choose a kind of certain value in order of a lottery. The results hold even after controlling for socio-economic variables.
urn:nbn:de:bsz:352-opus-11742
Keywords: D81; J16; 330; Decision-making under uncertainty; Gender differences; gambling